Valutazione dei costi di trattamento dei disturbi psicotici con olanzapina, risperidone e neurolettici tipici di un DSM italiano - Rossi, I.; Guidi, L. (Farmeconomia. Health Economics and Therapeutic Pathways, 2001)
Objective of the present retrospective analysis was to evaluate resources consumption for psychotic patients treatment with olanzapine (OLZ), risperidone (RIS) or typical neuroleptics (NL) during year 2000 in the Dipartimento di Salute Mentale (DSM) of Ravenna. The screening of total number of psychotic patients followed in the Ravenna DSM during year 2000 generated 26 cases treated with OLZ, 22 treated with RIS and 17 treated with NL that were respecting criteria of equivalence for age and illness severity. For these patients we analyzed pharmacological, non pharmacological (medical visits, nurse visits, social assistance, rehabilitative sessions) and hospital interventions during the year of observation, choosing the point of view of the DSM for costs attribution. The analysis of pharmacological interventions evidentiated a major usage of associated neuroleptics in the RIS and NL groups in respect to OLZ (p